Korelasi Faktor Iklim dengan Kejadian Demam Berdarah Dengue (DBD) di Kabupaten Boyolali Tahun 2020-2021 - Setyani, Hadining Dwi; Martini, Martini; Hestiningsih, Retno; Muh, Fauzi (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
In Boyolali Regency, incidence of Dengue Hemorraghic Fever (DHF) has been increasing over past three years. Descriptive epidemiological analysis needs to be conducted to describe the frequency of DHF cases and risk factors. Environmental factors are closely related to the transmission of DHF, one of which is climate factors. This study aimed to analyze the correlation of DHF incidence rate with climate factors (uch as rainfall, temperature, and humidity) This study was conducted based on DHF data collected from 2020 to 2021 from Boyolali District Health Office. Rank Spearman correlationt test. Was used to analyze the correlation between variables The result showed that there was a positive correlation between the rainfall with DHF incidence (p=0,012; r = 0,502). Meanwhile, there were no statistically correlation (p>0.05) between humidity, temperature with DHF incidence in Boyolali Regency. The finding serves as an input to DHF prevention and control programs.